2019
DOI: 10.1021/acs.jpcc.9b06899
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolutions of Vertically Aligned Two-Dimensional MoS2 Layers Revealed by in Situ Heating Transmission Electron Microscopy

Abstract: Benefiting from a large density of layer edges exposed on the surface, vertically aligned two-dimensional (2D) molybdenum disulfide (MoS2) layers have recently harvested excellent performances in the field of electrochemical catalysis and chemical sensing. With their increasing versatility for high-temperature, demanding applications, it is vital to identify their thermally driven structural and chemical stability, as well as to clarify its underlying principle. Despite various ex situ and in situ characteriza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 49 publications
3
24
0
Order By: Relevance
“…This study also reported that loss of Se resulted in the formation of large MoC clusters along the edges through the reaction of Mo atoms with C residue. Thermal decomposition was observed to begin at the surface‐exposed edge sites of vertically‐aligned 2D MoS 2 during in situ TEM heating in another study [85] . This work reported the decomposition of 2D MoS 2 to Mo nanoparticles due to the formation and propagation of voids by 950 °C.…”
Section: Structural and Chemical Transformations In Layered Chalcogenmentioning
confidence: 80%
See 1 more Smart Citation
“…This study also reported that loss of Se resulted in the formation of large MoC clusters along the edges through the reaction of Mo atoms with C residue. Thermal decomposition was observed to begin at the surface‐exposed edge sites of vertically‐aligned 2D MoS 2 during in situ TEM heating in another study [85] . This work reported the decomposition of 2D MoS 2 to Mo nanoparticles due to the formation and propagation of voids by 950 °C.…”
Section: Structural and Chemical Transformations In Layered Chalcogenmentioning
confidence: 80%
“…Thermal decomposition was observed to begin at the surface-exposed edge sites of vertically-aligned 2D MoS 2 during in situ TEM heating in another study. [85] This work reported the decomposition of 2D MoS 2 to Mo nanoparticles due to the formation and propagation of voids by 950°C. Recent work has also investigated the formation of inversion domains at temperatures above 700°C in monolayer MoS 2 using in situ heating ADF-STEM.…”
Section: Transformations Induced By Heatingmentioning
confidence: 95%
“…81 As a powerful advanced characterization technique, in situ TEM endows the possibility of direct visualization of the atomic-scale 2D layer structural dynamics on the small-length scales. 32,82 For instance, recent studies on horizontal MoS 2 or their monolayer counterparts via in-situ TEM have studied the kinetics of thermolysis-driven 2D MoS 2 layers growth via in-situ heating. 19,83 While previous Additionally, pronounced migrations of 2D MoS 2 layers at the junctions formed by multiple grains of large bending angles were observed, which is believed to be driven by the release of accumulating strain for reducing total interfacial energy.…”
Section: Atomic-scale In-situ Visualization Of Structural and Chemical Transitions In 2d Tmd Layersmentioning
confidence: 99%
“…19,83 While previous Additionally, pronounced migrations of 2D MoS 2 layers at the junctions formed by multiple grains of large bending angles were observed, which is believed to be driven by the release of accumulating strain for reducing total interfacial energy. 82 Moreover, it was identified that surface-exposed defective 2D layer edge sites are the triggering points for the thermal decomposition of S atoms and the subsequent decomposition of 2D MoS 2 layers. 82 Furthermore, Zhang et al achieved the controlled growth of vertically-aligned 2D WS 2 with high-temperature stability from in situ heating TEM investigations, as shown in Figure 12.…”
Section: Atomic-scale In-situ Visualization Of Structural and Chemical Transitions In 2d Tmd Layersmentioning
confidence: 99%
See 1 more Smart Citation